2016
DOI: 10.1016/j.talanta.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two passive samplers for the analysis of organophosphate esters in the ambient air

Abstract: a b s t r a c tBoth polyurethane foam (PUF) and sorbent-impregnated PUF (SIP) passive air sampling (PAS) methods were deployed and compared separately for the analysis of organophosphate esters (OPEs) in outdoor atmospheric environment. During an continuous period of 84 days, parallel samples were also collected by a high-volume active air sampler (HV-AAS) to assess the contamination levels and to calibrate uptake parameters of PAS. The total concentration of OPEs in both particulate and gaseous phases ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 37 publications
0
15
1
2
Order By: Relevance
“…136 Direct side-by-side comparisons showed that this indeed increased the uptake capacity of the sampler and increased t linear . 137,138 Use of SIPs since has focused on neutral peruoroalkyl substances [139][140][141][142][143][144][145][146] and organosiloxanes, 147-149 because these groups of SVOCs comprise some relatively volatile substances. However, SIPs are also being used for SVOCs that had previously been sampled with PUF-PASs 150-152 as well as organophosphate esters 138 and ionic peruoroalkyl substances.…”
Section: D23 Samplers Based On Polydimethyl Siloxane (Pdms)mentioning
confidence: 99%
See 1 more Smart Citation
“…136 Direct side-by-side comparisons showed that this indeed increased the uptake capacity of the sampler and increased t linear . 137,138 Use of SIPs since has focused on neutral peruoroalkyl substances [139][140][141][142][143][144][145][146] and organosiloxanes, 147-149 because these groups of SVOCs comprise some relatively volatile substances. However, SIPs are also being used for SVOCs that had previously been sampled with PUF-PASs 150-152 as well as organophosphate esters 138 and ionic peruoroalkyl substances.…”
Section: D23 Samplers Based On Polydimethyl Siloxane (Pdms)mentioning
confidence: 99%
“…137,138 Use of SIPs since has focused on neutral peruoroalkyl substances [139][140][141][142][143][144][145][146] and organosiloxanes, 147-149 because these groups of SVOCs comprise some relatively volatile substances. However, SIPs are also being used for SVOCs that had previously been sampled with PUF-PASs 150-152 as well as organophosphate esters 138 and ionic peruoroalkyl substances. 153 The idea of adding XAD to a sorbent to increase its uptake capacity has since been used also for lter paper 154 and PDMS sheets.…”
Section: D23 Samplers Based On Polydimethyl Siloxane (Pdms)mentioning
confidence: 99%
“…We used an average uptake rate of 3.3m 3 /d for calculating the concentrations of OPFR in air sample as suggested by Liu et al. [4]. Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…SIP-PAS的R值可通过AAS校正法 [75,79] , 直接引用 PUF-PAS采样速率法 [54] 、DCs校正法 [26,77] 得到. 不同 研究中AAS校正法估算的SIP-PAS的R值(m [75,78~80] .…”
Section: Xad-4树脂浸渍的puf盘被动采样器unclassified
“…SIP-PAS与PUF-PAS的PUF盘几何尺寸相同, 因此PUF-PAS、SIP-PAS 同时进行采样时, 通过DCs法获得PUF-PAS的R值, 也 可同时应用于SIP-PAS [54] . 也有研究用DCs法分别校正 SIP-PAS和PUF-PAS的R值, Liu等 [26] 用SIP-PAS、PUF- .…”
Section: Xad-4树脂浸渍的puf盘被动采样器unclassified